2020
DOI: 10.1080/26895293.2020.1835740
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of fungal pathogens associated with leaf spot disease of date palms (Phoenix dactylifera)

Abstract: Date palm is the most important crop in Oman, occupying approximately 50% of the area devoted to agriculture. Little information is available on leaf spot diseases of date palm in Oman and in the world. This study was conducted to identify the most common fungal pathogens associated with leaf spot diseases of date palm. A total of 198 symptomatic leaf samples were collected from seven districts in Oman. Isolations revealed that most isolates belonged to the genus Alternaria. Molecular-based identification usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 58 publications
2
20
1
Order By: Relevance
“…On the other hand, they reported that strains of A. burnsii and A. tomato were highly pathogenic, but we did not detect these species in our study (Al-Nadabi et al, 2020).…”
Section: Pathogenicity Testcontrasting
confidence: 94%
“…On the other hand, they reported that strains of A. burnsii and A. tomato were highly pathogenic, but we did not detect these species in our study (Al-Nadabi et al, 2020).…”
Section: Pathogenicity Testcontrasting
confidence: 94%
“…This formed six experimental groups, which are described in Table 1. The pepper seedlings were exposed to selected biotic stresses, and sampling was performed after eight days [53,54]. The harvested samples were either immediately used or rapidly deactivated in liquid nitrogen and stored at −80 • C. The moisture level (70%), pH value (~7), and EC (≤1.2) of the bulk soil samples were recorded before the pot experiment.…”
Section: Experimental Designmentioning
confidence: 99%
“…2394 and Thieloviopsis sp. 2107, used in this work, came from the previous collections of Al-Nadabi et al (2020). These fungal pathogens were isolated from date palm leaves infected with leaf spot disease collected from different governorates of Oman.…”
Section: Fungal Pathogensmentioning
confidence: 99%